Circadian rhythms and food preference search of Pseudoplusia includens caterpillars (Walker) (Lepidoptera: Noctuidae) - Souza Oliveira, Ana Paula; Silva dos Santos, Régis Sivori; Carissimi Boff, Mari Ines (Comunicata Scientiae, 2013)
An understanding of behavior patterns that are fundamental to the biology of pest insects is arequisite for implementation of control strategies. This study aims to evaluate the circadian rhythms ofPseudoplusia includens larvae in four different natural diets. The study was conducted in laboratoryfor 48 hours hourly. The experimental design was randomized with four treatments (leaf discs) and tenreaplications with free choice. The treatments were: leaves of Rumex obtusifolius, Trifolium repens,Plantago lanceolata and Malus domestica. The caterpillars visited more leaves of T. repens and R.obtusifolius than the leaves of M. domestica and P. lanceolata. The searching activity lasted for the48 hours of the observation during the 24 hours and the increase in the searching activity occurredbetween 16 to 21 hours.